Increasing customer orientation in retail category strategy : Case study in retail - Vahtola, Niko (My University, 2022)
Customer orientation is often raised as a key element in retailing. Still, it is often practiced only in stores, marketing departments and product development when it should be on the agenda of the whole company and its operations. In order to identify and prioritize the right investment decisions, retailers must understand what factors and improvements are valued by consumers and thus bring competitive advantage to the company. The theoretical model for category management decision-making includes four strategic elements of category management: assortment planning, pricing, space management, and promotional activities. The model links these strategic elements to key consumer value drivers by recognizing the category management decisions that are affecting the consumer decision-making criteria. These key consumer value drivers are product, price, place, and promotion, which are the basis for consumer decision-making criteria. In this study, the five most important purchasing criteria for consumers were high-quality products, low prices, large product range, most convenient store locations, and items always in stock. From these five criteria, the case company had the weakest performance in low prices, most convenient store locations, and items are always in stock that where further examined. The impact of decision-making criteria on customer satisfaction and loyalty is examined using regression models. From the examined three consumer decision-making criteria, items are always in stock were a relatively influential factor for consumer satisfaction and loyalty in all three customer groups: current customers, potential customers, and potential customers top 25%. Also, low prices was a relatively influential factor for potential customers and potential customers top 25%. Therefore, the case company could better serve its current customers and attract new customers by focusing on availability levels and developing the assortment of cheaper products. By focusing on these topics, the case company could gain more market share and revenue, but these benefits should still be evaluated together with the potential losses in profitability.

Asiakaslähtöisyys nostetaan usein avaintekijäksi vähittäiskaupassa. Asiakaslähtöisyyttä kuitenkin harjoitetaan usein lähinnä myymälöissä, markkinointiosastoissa ja tuotekehityksessä, kun sen pitäisi olla koko yhtiön ja sen operaatioiden taustalla. Jotta yritys voi tunnistaa ja priorisoida tärkeimpiä investointipäätöksiä, sen tulisi ymmärtää mitkä tekijät ja kehityskohdat luovat arvoa asiakkaan näkökulmasta ja näin ollen luovat yritykselle kilpailuetua. Kategoriajohtamisen päätöksenteon teoreettinen viitekehys sisältää neljä kategoriajohtamisen strategista elementtiä: valikoiman suunnittelu, hinnoittelu, tilanhallinta ja myynnin-edistämistoimenpiteet. Viitekehys linkittää nämä strategiset elementit asiakkaan tärkeimpiin arvoajureihin tunnistamalla kategoriajohtamisen operaatiot, joilla pystytään vaikuttamaan näihin kuluttajien arvoajureihin. Kuluttajien arvoajureiksi tunnistetaan tuote, hinta, paikka ja promootio, jotka ovat perustana kuluttajien päätöksenteon kriteereille. Tutkimuksessa nousi esiin viisi tärkeintä kuluttajien ostopäätöskriteeriä, jotka ovat korkealaatuiset tuotteet, matalat hinnat, laaja tuotevalikoima, tuotteiden hyvä saatavuus, sekä hyvät myymäläsijainnit. Näistä viidestä kriteeristä kohdeyhtiö suoriutui heikoiten matalissa hinnoissa, hyvissä myymäläsijainneissa ja tuotteiden saatavuudessa, minkä vuoksi näihin kriteereihin kiinnitettiin erityistä huomiota. Kuluttajien ostopäätöskriteereiden vaikutusta asiakastyytyväisyyteen ja -lojaaliuteen tarkastellaan regressiomallien avulla. Tarkemmin tutkituista kolmesta ostopäätöskriteeristä tuotteiden hyvä saatavuus oli verraten merkittävä tekijä asiakastyytyväisyyden ja -lojaaliuden kehittämisessä kaikissa tutki-tuissa asiakaskohderyhmissä: nykyiset asiakkaat, potentiaaliset asiakkaat ja potentiaaliset asiakkaat parhaat 25 %. Tämän lisäksi halvat hinnat olivat myös verraten tärkeä tekijä potentiaalisten asiakkaiden ja potentiaalisten asiakkaiden parhaan 25 prosentin asiakasryhmissä. Näin ollen, kohdeyhtiö pystyisi palvelemaan paremmin nykyisiä asiakkaitaan ja houkuttelemaan uusia asiakkaita keskittymällä tuotteiden saatavuuteen ja kehittämällä edullisempien tuotteiden valikoimaa. Keskittymällä näihin teemoihin, kohdeyhtiö pystyisi mahdollisesti kasvattamaan markkinaosuuttaan ja liikevaihtoaan, mutta näitä hyötyjä tulisi arvioida yhdessä mahdollisten kannattavuushaittojen kanssa.
Keywords: Category management, retail, decision-making, customer orientation